Strategi Komunikasi Guru Kepada Siswa Kelas 5 SDN 01 Cisangu dalam Meningkatkan Kemampuan Literasi Digital - Murtiadi, Murtiadi; Fitriyanto, Fitriyanto; Mutiara, Mutiara (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
SDN 01 Cisangu is one of the elementary school education units in Bengkok Village, Cisangu Village, Cibadak Sub-district, Lebak Regency, Banten Province. SDN 01 Cisangu is under the auspices of the Ministry of Education and Culture. This study aims to describe the communication strategies applied by teachers in an effort to improve the digital literacy skills of grade 5 students. In this study using qualitative research methods with a descriptive approach. Data collection techniques were carried out by means of observation, interviews, and documentation. The results show that teachers use a variety of effective communication strategies in teaching digital literacy, including the use of digital media, interactive approaches and providing constructive feedback. These strategies enable students to be engaged and active in the learning process, as well as improve their understanding and skills in digital literacy. This finding is in line with Joseph A. Devito's theory of interpersonal communication, which states that effective interpersonal communication is characterized by several features, namely openness, empathy, support, positivity and equality. Teachers at SDN 01 Cisangu demonstrate these traits in their interactions with students, which helps to create a supportive and effective learning environment. Teachers' openness in conveying information and listening to students, empathy in understanding students' needs and difficulties, support and positivity in providing constructive feedback all contribute to improving students' digital literacy.